The elements of life: A biocentric tour of the periodic table - Remick, Kaleigh A.; Helmann, John D. (Advances in microbial physiology, 2023)
Living systems are built from a small subset of the atomic elements, including the bulk macronutrients (C,H,N,O,P,S) and ions (Mg,K,Na,Ca) together with a small but variable set of trace elements (micronutrients). Here, we provide a global survey of how chemical elements contribute to life. We define five classes of elements: those that are (i) essential for all life, (ii) essential for many organisms in all three domains of life, (iii) essential or beneficial for many organisms in at least one domain, (iv) beneficial to at least some species, and (v) of no known beneficial use. The ability of cells to sustain life when individual elements are absent or limiting relies on complex physiological and evolutionary mechanisms (elemental economy). This survey of elemental use across the tree of life is encapsulated in a web-based, interactive periodic table that summarizes the roles chemical elements in biology and highlights corresponding mechanisms of elemental economy.